Emergence of antibiotic resistant Shigella species: A matter of concern. Issue 4 (July 2018) - Puzari, Minakshi; Sharma, Mohan; Chetia, Pankaj
Abstract: A major threat to the world is the emergence of antibiotic resistant bacteria, which has rendered previously susceptible drugs useless and increased the rate of therapeutic failures. Shigella species, which are the causative organism of Shigellosis, were earlier susceptible to ampicillin, chloramphenicol, co-trimoxazole and nalidixic acid but now they have developed resistance against fluoroquinolones, cephalosporins and azithromycin. Many shigellosis outbreaks have been reported by resistant strains of Shigella species. This review attempts to provide a brief overview about the scenario of shigellosis and the emergence as well as ubiquitous nature of multidrug resistant (MDR) Shigella species.